2016
DOI: 10.1111/bju.13540
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of 68Gallium‐prostate‐specific membrane antigen positron emission tomography/computed tomography for preoperative lymph node staging in prostate cancer

Abstract: In patients with intermediate- to high-risk PCa, 68Ga-PSMA PET/CT had a high specificity and a moderate sensitivity for LNM detection. 68Ga-PSMA PET/CT had the potential to replace current imaging for LN staging of patients with PCa scheduled for RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
155
4
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(176 citation statements)
references
References 26 publications
11
155
4
6
Order By: Relevance
“…Nine patients with LNs found positive by histopathology but negative by 68 Ga-PSMA-11 PET harbored only micrometastases in single LNs (mean size of negative LNs, 3 mm). Impaired detection of LN metastases smaller than 5 mm was anticipated and was also reported by other groups with similar results for the overall performance of 68 Ga-PSMA-11 PET for node staging (81,94,95).…”
Section: Primary Stagingsupporting
confidence: 85%
See 1 more Smart Citation
“…Nine patients with LNs found positive by histopathology but negative by 68 Ga-PSMA-11 PET harbored only micrometastases in single LNs (mean size of negative LNs, 3 mm). Impaired detection of LN metastases smaller than 5 mm was anticipated and was also reported by other groups with similar results for the overall performance of 68 Ga-PSMA-11 PET for node staging (81,94,95).…”
Section: Primary Stagingsupporting
confidence: 85%
“…Evidence that PSMA ligand PET imaging significantly affects management in patients with early BCR is increasing. In a homogeneous cohort of 70 patients who had a PSA level of less than 1 ng/mL and were potential candidates for salvage radiation treatment, 68 Ga-PSMA-11 PET/CT led to a major change in management (disease in LN or bone not covered by the conventional radiation therapy field) for 28.6% of patients (81). In an additional 26% of patients, the disease was confined to the prostate bed, possibly defining these patients as optimal candidates for salvage radiation therapy.…”
Section: Psma Ligand Imaging Biochemical Recurrencementioning
confidence: 99%
“…On template-based analysis, the sensitivity, specificity, and accuracy were 68.3%, 99.1%, and 95.2% for 68 Ga-PSMA-11 PET and 27.3%, 97.1%, and 87.6% for morphologic imaging, respectively (21). Similar results on the diagnostic efficacy of PSMA ligand PET for the detection of nodal metastases were obtained in other studies (47,49). For bone metastases, Pyka et al demonstrated that 68 Ga-PSMA-11 PET significantly outperformed bone scanning because of both its high sensitivity and its high specificity on a patient and region basis (P 5 0.006 and P , 0.0001, respectively).…”
Section: Primary Stagingsupporting
confidence: 80%
“…In detecting sites of nodal or bone involvement in preoperative patients, cross-sectional imaging has shown a limited pooled sensitivity and specificity of 42% and 82%, respectively, for CT and 39% and 82%, respectively, for MRI (3), as up to 80% of lymph node metastases in PC are harbored in normal-sized lymph nodes (2). Several studies showed a clear superiority of PSMA ligand PET/CT over standard-of-care imaging (CT, MRI, or bone scanning) (21,(46)(47)(48)(49). For example, in a retrospective analysis of 130 patients with primary intermediate-to high-risk PC using templatebased pelvic histopathology as a reference, 68 Ga-PSMA-11 PET performed significantly better than morphologic imaging for N staging both on a patient and a template basis (P 5 0.002 and , 0.001, respectively).…”
Section: Primary Stagingmentioning
confidence: 99%
“…Several previous studies have evaluated and shown a high diagnostic performance of Ga-68 PSMA PET/CT in the detection of local and distant disease, with a higher sensitivity compared to other radiopharmaceuticals such as radiolabeled choline [12][13][14][15][16]. However, few studies investigated the diagnostic performance of radiolabeled PSMA for primary LN staging in newly diagnosed, intermediate to high-risk PCa patients with various sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%